Consumer response to brand involved in food safety scandal: An exploratory study based on a recent scandal in India. Issue 1 (20th July 2017) - Roy, Vivek; Tata, Sai Vijay; Parsad, Chandan
Abstract: This paper focuses on the product‐harm oriented brand crisis situation from the perspective of food safety scandal. Food safety scandals cause the deterioration of consumer confidence and thereby affect consumer food choices. However, there exists a lack of studies that examine the consumer response to a brand involved in a food safety scandal. The main research questions addressed are (a) to explicate a detailed mechanism of the consumer response towards a brand involved in food safety scandal and (b) what prompts a consumer to trust the faulty brand again. Further, this study presents empirical contextualization from a real brand‐specific food safety scandal, the 2015 monosodium glutamate scandal of Nestlé Maggi noodles in India. The study is based on 308 Indian consumers and employs structural equation modeling to analyze the data. The results show that the emotional attachment with the brand forms the basis of the restoration of brand trust by enhancing the authenticity perception of the brand among consumers. This, in turn, forms the basis for the enhancement of healthiness perception of ingredients in order to restore the purchase intention and mitigate blame attribution among consumers. The results are further analyzed from the brand perspective to outline critical implications toward food brand crisis management. This study is among the initial studies to focus on the aftermath of food safety scandals from the brand and consumer perspective.